2019
DOI: 10.1007/s10763-019-10000-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Materialist Vision of ‘Learning as Making’: the Case of 3D Printing Pens in School Mathematics

Abstract: In this paper, we build on a previously developed notion of 'learning as Making' to examine mathematics thinking and learning in a highly transformative and technological Making environment: one that involves a handheld 3D printing technology which enables 3D models to be created instantly via one's moving hand. In particular, we present two examples of Maker-centred lessons for teaching and learning of primary mathematics. In these lessons, the students actively constructed artefacts with 3D Printing Pens whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Besides the above example, I also explored other possibilities for teaching and learning mathematics as enabled by constructionist pedagogy with 3D Pens. Given that the 3D Pens allows for diagramming and manipulating with the 3D models, there are a number of mathematics topics that the 3D Pens could be complementary to teaching and learning, In the primary school level, for example, I designed lessons with classroom teachers for teaching the number of faces, edges and vertices of prisms and pyramids (Ng & Ferrara, 2020). It was found that the students' visualization of 3D solids was inextricably linked to their hand movements in Making (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above example, I also explored other possibilities for teaching and learning mathematics as enabled by constructionist pedagogy with 3D Pens. Given that the 3D Pens allows for diagramming and manipulating with the 3D models, there are a number of mathematics topics that the 3D Pens could be complementary to teaching and learning, In the primary school level, for example, I designed lessons with classroom teachers for teaching the number of faces, edges and vertices of prisms and pyramids (Ng & Ferrara, 2020). It was found that the students' visualization of 3D solids was inextricably linked to their hand movements in Making (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the past five years, I have been actively engaging in classroom-based interventions with primary and secondary school mathematics teachers to develop a technologyenhanced constructionist pedagogy, termed 'learning as making' (Ng & Chan, 2019;Ng & Ferrara, 2020). The notion of 'learning as making' is rooted in Seymour Papert's (1980) revolutionary theory of constructionism, which suggests that knowledge is not delivered to the learner, but is rather constructed through activities, in particular, by producing a physical and shareable product.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the 3D Pen environment supported hands-on and flexible constructions of the 3D solids. For example, when constructing a triangular prism with 3D Pens, some students created a triangular base initially, whereas some students created one of its rectangular faces initially (Ng & Ferrara, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, 3D DGEs enable learners to construct, observe, and manipulate geometrical figures in a "3D-like space," through which their perception of spatial positions and spatial relations can be strengthened (Christou, Jones, Mousoulides, & Pittalis, 2006). On the other hand, the first author (Ng & Chan, 2019;Ng & Ferrara, 2019) has previously examined a Papert-inspired, "learning as Making" pedagogy, one that facilitates geometry learning with the hands-on construction of physical artefacts in a 3D printing environment. The author concluded that the use of 3D Printing Pens 1 provides low-floor, high-ceiling opportunities for students to utilize their hands to develop their spatial skills and enhance integrated STEM learning (Ng & Chan, 2019).…”
mentioning
confidence: 99%
“…By contrast, the artefact construction dimension of problem-solving contextualised with physical inputs or outputs in this study (i.e. make a device that could detect prime numbers) is very rarely presented in mathematics classrooms (Ng & Chan, 2019;Ng & Ferrara, 2020). Without explicitly stating what to do with the LED lights, the students needed to prepare the problem by setting up scenarios for how to display their results upon checking whether a number was a prime or not.…”
Section: On Preparing Problemsmentioning
confidence: 96%